2018
DOI: 10.1111/tbj.13034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the 2009 USPSTF breast cancer screening recommendations on breast cancer in Michigan: A longitudinal study

Abstract: In 2009, the revised United States Preventive Services Task Force (USPSTF) guidelines recommended against routine screening mammography for women age 40-49 years and against teaching self-breast examinations (SBE). The aim of this study was to analyze whether breast cancer method of presentation changed following the 2009 USPSTF screening recommendations in a large Michigan cohort. Data were collected on women with newly diagnosed stage 0-III breast cancer participating in the Michigan Breast Oncology Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In accordance with previous literature [2,3,8,10,11], our study demonstrates that patients with symptomatic breast cancer tend to be significantly younger (49% of women with symptomatic cancer were 50 years compared to 13% of screen-detected patients). This observation is attributed, at least in part, to the widespread adoption of screening mammography in women over 50.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous literature [2,3,8,10,11], our study demonstrates that patients with symptomatic breast cancer tend to be significantly younger (49% of women with symptomatic cancer were 50 years compared to 13% of screen-detected patients). This observation is attributed, at least in part, to the widespread adoption of screening mammography in women over 50.…”
Section: Discussionsupporting
confidence: 92%
“…Detection methods vary with age. Young women (<50 years) are more likely to present with palpable tumors, whereas identification of cancer by screening mammography increases with age [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer also has a successful screening modality, namely mammography, and suffers from similar poor outcomes when associated with an ED visit, 11.9% mortality vs 3.4%, ED to non-ED associated. 21 Prostate cancer screening is controversial and recommendations vary by organization and country, regardless, a screening modality is available and those diagnosed with prostate cancer associated with an ED visit have higher mortality than those that don’t (13.2% vs 3.5%). 22 Lastly, cervical cancer also is frequently screened for as outpatients and 22% of those seen in the ED were dead, versus 7.4% of those not seen in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a number of hormones such as E1, E2 and FSH. in females can promote the proliferation and invasion of cancer cells, and that their mechanism of actions may be related to the activation of proteins, enzymes or oncogenes involved in nucleic acid synthesis which promotes tumorigenesis [13][14].…”
Section: Discussionmentioning
confidence: 99%